The Effect of Transformational Leadership and Work Discipline on Employee Performance of PT Jaya Abadi Siaga With Organizational Support as an Intervening Variable - Kuni Inayati; Darmilisani; Kholilul Kholik (Cattleya Darmaya Fortuna, 2026)
his study aims to analyze the effect of transformational leadership and work discipline on employee performance with organizational support as an intervening variable at PT Jaya Abadi Siaga Medan. This research uses a quantitative approach with an associative research type. The population in this study consists of all employees of PT Jaya Abadi Siaga Medan, totaling 60 individuals. The sampling technique used is the census method, in which the entire population is used as the research sample. The data analysis technique employed is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS software. The results of the study indicate that transformational leadership has a positive and significant effect on organizational support and employee performance. Work discipline has a positive and significant effect on organizational support, but does not have a significant effect on employee performance. Organizational support has a positive and significant effect on employee performance. Furthermore, organizational support is able to mediate the effect of work discipline and transformational leadership on employee performance. Thus, it can be concluded that organizational support plays an important role in improving employee performance, both directly and as an intervening variable.